Phytochemistry, antioxidant and biocide activity of Parthenium hysterophorus L. vs Artemia salina L. - Alejandre-Rosas, Jorge Alberto; Gallegos-Robles, Miguel Ángel; González-Salas, Uriel; González-Jacob, Antonio; García-Hernández, José Luis; Murillo-Amador, Bernardo (Revista Mexicana de Ciencias Agrícolas, 2025)
The importance of medicinal plants is highlighted, mentioning that 80% of the world’s population uses traditional medicine (WHO). Mexico is the second richest country in knowledge of traditional medicine, after China. Parthenium hysterophorus L., known as the bitter broom, is mentioned, and although its use in Mexico is not widely documented, it has been recorded in Papantla, Veracruz and Güémez, Tamaulipas. The study focuses on the phytochemistry of P. hysterophorus, identifying secondary metabolites, such as alkaloids, flavonoids, saponins, and tannins. Antioxidant activity was evaluated using the DPPH method, showing high percentages of inhibition in aqueous and ethanolic extracts. In addition, the biocidal activity in Artemia salina was analyzed, revealing moderate toxicity for the aqueous and ethanolic extract. The plant material was collected in the central area of the state of Veracruz in July 2022. The results suggest a potential therapeutic and pharmacological use of the plant, and a use in crop protection; nevertheless, more research is needed to better understand its phytochemistry and medical applications.
Keywords: Medicinal plants; natural products; biological activity; free radicals